2020
DOI: 10.1007/s42452-020-03381-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiC/Si3N4 micro-reinforcement on mechanical and wear properties of friction stir welded AA6061-T6 aluminum alloy

Abstract: Friction stir welding (FSW) is extensively used to join aluminum alloys components for applications in structural, aviation and automotive sectors. In this investigation, the mechanical properties (tensile strength, percentage elongation, and microhardness), abrasive wear properties and microstructure of friction stir welded joint of AA6061-T6 were studied by inter-plate reinforcing of silicon carbide microparticles (µSiC) and silicon nitride microparticles (µSi 3 N 4). The friction stir welding was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…12 . Figure 10 reveals that the tensile strength of coated edge (TiB2 reinforced) joint is higher than the non-coated (unreinforced) edge joint due to the presence of TiB2 in the welded zone 36 , 37 , 39 , 41 , 42 . Furthermore, the tensile strength of the non-coated edge sample welded at the rpm of 1400 exhibits higher strength than the sample welded at 2240 rpm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 . Figure 10 reveals that the tensile strength of coated edge (TiB2 reinforced) joint is higher than the non-coated (unreinforced) edge joint due to the presence of TiB2 in the welded zone 36 , 37 , 39 , 41 , 42 . Furthermore, the tensile strength of the non-coated edge sample welded at the rpm of 1400 exhibits higher strength than the sample welded at 2240 rpm.…”
Section: Resultsmentioning
confidence: 99%
“…However, the impact strength was lower due to weak bonding between parent and reinforcement materials. A similar technique was also used by Kumar et al 36 to introduce SiC and Si3N4 particulates in the friction stir weld zone. Dragatogiannis et al 37 machined a rectangular grove whose depth was half of the plate depth along the joint line for the fabrication of TiC reinforced friction stir weld joint.…”
Section: Introductionmentioning
confidence: 99%
“…FSW system generally includes three events like heating, deformation and forging and the generated heat causes the flow of materials from the forward side of the tool to the backward side of the tool [4]. FSW will be a preferred method of welding not just to aluminium alloys [5], but also magnesium alloys [6], titanium alloys [7], metal matrix composites [8], and other difficult metals such as stainless steel [9]. The advancing side and retreating side play a significant role in FSW among specific alloys [10].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Balaji et al [11] demonstrated that samples of FSW AA6063 similar joints produced with the addition of B 4 C powder show higher hardness and impact properties than the un-reinforced ones, while the tensile behaviour worsens when the reinforcement is present. Similarly, Kumar et al [12] investigated the effect of reinforcing particles addition into an AA6061 alloy, finding that the size and type of the particles significantly influence and, in most cases, enhance the hardness and wear behaviour of the joint while decreasing its tensile properties. Nevertheless, most researchers agree that adding reinforcing particles in similar aluminium joints improve the static mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The Charpy impact test is another very useful and straightforward experimental method to assess the effect of process parameters and microstructure on the impact strength of metallic materials [15] and, in particular, of aluminium alloys [16][17][18][19][20][21][22]. To the author's knowledge, to date the impact behaviour of similar and dissimilar FSWed aluminium alloys has not been deeply studied [12,16,23,24]. In the automotive/aerospace field, the need for high resistant and low-density joints is very strictly; to this objective, dissimilar AA2024-AA7075 joints have been deeply investigated [25][26][27] but no data are available in literature as concern impact strength and the influence of reinforcing particles in the absorbed energy.…”
Section: Introductionmentioning
confidence: 99%